SSR based characterization of peach (Prunus persica L.) and apricot (Prunus armeniaca L.) varieties cultivated in Hungary - Bedő, Janka; Baris, Eren; Szani, Zsolt; Surányi, Dezső; Kiss, Erzsébet; Veres, Anikó (Acta Agraria Debreceniensis, 2018)
The SSR (Simple Sequence Repeat) markers allow the discrimination of the cultivars and determination its specific DNA fingerprints. The aim of this research was to evaluate fifteen apricot (Prunus armeniaca L.) and fifty-one peach (Prunus persica L.) genotypes cultivated in Hungary to obtain their DNA fingerprints in 6 SSR (Simple Sequence Repeats) loci by allele numbers and sizes. DNAs were extracted from leaves. PCR was carried out with CY-5 fluorescent labeled Prunus microsatellite markers and the products were separated on polyacrylamide gel with ALF (Automated Laser Flourometer)-Express II. According to our results, in the case of peach genotypes, all 6 SSRs were able to amplify alleles. UDP 96 005 was the most informative marker and UCDCH 17 was the least due to its monomorphic pattern. Regarding the apricot samples BPPCT 041 did not amplify any allele. In the case of P. armeniaca UDP 96 005 had the highest heterozygosity index as well and the highest number of alleles. The least informative marker was the UCDCH 17. Since the 6 SSR were not enough to discriminate the apricot and peach genotypes, it is suggested to use more SSR primers.